Causality Relationship between Crude Oil Variables and Budget Variables in Malaysia - Zakaria, Zukarnain; Shamsuddin, Sofian (International Journal of Energy Economics and Policy, 2017)
As an oil and gas exporter, Malaysia profited from higher world energy prices. However, the fall in oil prices from highs in 2014 significantly affected Malaysia’s government revenue, hence its expenditure since the Malaysian government revenue still largely depends on oil revenues. Malaysia also has problems with high spending on energy subsidy, shrinking in its net crude oil export, and narrowing the gap between its crude oil production and consumption. Given this scenario, not only shocks in crude oil price could affect Malaysian government revenue and expenditure, but also other variables such as crude oil production, export, import, and consumption. However, the long-term impact of these crude oil variables on Malaysia’s government revenue and expenditure is still empirically unclear. Therefore, the main objective of this paper is to examine the causality relationship between crude oil variables and budget variables in Malaysia. The findings show that crude oil variables studied have no long run causality relationship with government expenditure but significantly cause the Malaysian government revenue in the long run. In short run, however, only crude oil consumption was found to Granger causes government expenditure thus indicates the impact of fuel subsidy on the government expenditure. For government revenue, there is short-run causality running from production, export and import to the government revenue. Keywords: Oil Prices, Government Expenditures, Budget deficit, Malaysia JEL Classifications: 043, Q43, Q47